Supervision and Law Enforcement to Increase Taxpayer Compliance at the Pondok Aren Tax Office - I Gede Komang Chahya Bayu Anta Kusuma; Supriyadi; Irwan Aribowo; Ary Widiastuti (PT Keberlanjutan Strategis Indonesia, 2026)
This study analyzes the influence of supervision and law enforcement on improving taxpayer compliance at the Pondok Aren Tax Office (KPP Pratama), focusing on post-audit Taxable Entrepreneurs (PKP). The approach used was qualitative with descriptive-analytical methods, through data collection from interviews (tax officers and taxpayers) and surveys to identify factors influencing post-audit compliance. The study results indicate that stricter supervision and effective law enforcement have the potential to improve compliance, but their implementation still faces significant obstacles such as limited resources, weak taxpayer understanding of tax obligations, and the effectiveness of sanctions that have not yet provided an adequate deterrent effect. The findings also emphasize the importance of more intensive education and outreach for new PKPs and the need to improve internal coordination (for example, between the supervisory and audit functions) to ensure more targeted post-audit follow-up. Key recommendations include strengthening technology-based supervision systems, improving tax counseling, and stricter law enforcement, including the option of freezing electronic certificates to suppress repeated violations and encourage ongoing compliance.